Effects of drying temperature on the amount of secondary metabolites and antioxidant activity of Orthosiphon aristatus (Blume) miq. tea extracts - Taokaenchan, Narin; Satienperakul, Sakchai; Ueda, Yuto; Tsutsumi, Shuhei; Yasuda, Shin (Vol. 150, No. 4 (August 2021) pages 735-742.)
"Orthosiphon aristatus (Blume) Miq. Tea is a traditional herbal tea in Thailand. This herb is used to prevent and treat a wide range of disease such as diuresis, hypertension, and diabetes. In this study, three different drying temperatures used for herbal tea processing were evaluated (40, 50, and 60°C) for their secondary metabolites [total phenolic content (TPC), caffeic acid (CA), rosmarinic acid (RA), and total flavonoid content (TFC)] and antioxidant activity"-Title page.